Multimedia Game : Dam Ular for kindergarten / Hanee Norelny Jemain - Jemain, Hanee Norelny (2006)
Last ten years we have seen explosive growth of computer technology used for learning in schools, universities, business industries and professions. Consequently, the quantity of educational software has increased dramatically. The multimedia capabilities today's are advanced as a platform to give a better performance in learning especially learning in mathematics." Dam Ular" multimedia game was introduced to kindergarten on learning mathematics in different dimension which is focus on additional and subtraction, hi developing the courseware, methodology that used is ADDIE Model which is consists of analysis, design, development, implementation, evaluation. The data is collected through doing a research on existing journal and similar courseware. "Dam Ular" game is developing in an interactive form that allows the children to participate in the learning process. The children can learn mathematics by answering the questions provided besides having full of fun.